Explaining Transformational Leadership with Emphasis on Quality of Work Life and Professional Commitment of Medical Sciences Employees in Iran - Shabani , Majid; Mohammadi , Nabiollah; Mokhtari Bayekolaei , Mehran; Gilanipour, Javad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The primary objective of the present study is to explain transformational leadership with an emphasis on the quality of work life and the professional commitment of employees in the medical sciences field in Iran. Methodology: The research method in this study is descriptive-survey and is applied in terms of its goal. The statistical population of this research includes the employees of Iran’s medical sciences sector. To determine the sample size, the Morgan sample size estimation table was used, resulting in a selection of 220 individuals as the statistical sample. The sampling method in this research is simple random sampling. Data collection tools include questionnaires. The reliability of the research questionnaires was confirmed using Cronbach’s alpha coefficient. Confirmatory factor analysis was used to assess the validity of the questionnaires. Data analysis was conducted using LISREL software. Findings: The research findings indicate that the quality of work life and professional commitment of employees lead to the growth and improvement of transformational leadership. Conclusion: Based on the research results, it is suggested that managers engage in discussions with employees about their fundamental beliefs and values and, as much as possible, recruit new employees whose goals and aspirations align sufficiently with those of the organization.